Biofortification of wheat (Triticum aestivum L.) genotypes with zinc and manganese lead to improve the grain yield and quality in sandy loam soil - Dhaliwal, Salwinder Singh; Sharma, Vivek; Shukla, Arvind Kumar; Behera, Sanjib Kumar; Verma, Vibha; Kaur, Manmeet; Singh, Prabhjot; Alamri, Saud; Skalicky, Milan; Hossain, Akbar (Frontiers in Sustainable Food Systems, 2023)
Introduction Micronutrients particularly Zn and Mn play a vital role in agricultural plants as well as human beings. Categorization of existing genotypes in wheat toward Zn and Mn application is extremely important to select the most efficient Zn as well as Mn genotype with higher yield and quality. Methods In this study, the differentiation of 14 genotypes was done for nutrient use efficiency characteristics through two methods to identify the most efficient Zn and Mn wheat genotypes. The categorization of genotypes was done based on efficiency and responsiveness under control and Zn + Mn treated conditions. Results and discussion The mean values of plant growth parameters, crop yield, nutrient concentration (Zn, Mn, N, P and K), quality parameters (crude fiber and protein content) and nutrient utilization efficiency were considerably greater in Zn + Mn treated plots signifying the higher response of traits toward Zn and Mn application. The interaction between genotype and Zn + Mn indicated that the application of Zn + Mn significantly affected the studied genotypes for different characteristics. The results of the study indicated that genotypes PBW-824, BWL-8855, PBW-872, PBW-869 and PBW Zn1 were efficient in terms of crop yield. Based on the quality parameters, genotypes PBW-824 and PBW-869 were the highest ranked among the studied genotypes. The identified Zn + Mn efficient genotypes would be valuable resources for higher crop production along with improved wheat grain quality.